A Study of Functionality of Mold for Bladder Assisted Composite Manufacturing (BACM) - WATAN, MUHAMMAD ABDUL MUJIB BIN ASHARI (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Composite manufacturing faces challenges in producing complex, hollow components with good mechanical performance. Current methods like injection/compression moulding are cost-effective but often have poorer mechanical performance. Continuous fibre reinforced materials are used in high-strength areas like defense and aerospace. The BACM mould offers a unique method for shaping composite structures, allowing precise control over pressure and forces during curing. This study aims to provide insights on the BACM mold's capabilities and applications, paving the way for advanced manufacturing and composite materials.